PENGEMBANGAN ENSIKLOPEDIA DIGITAL BANGUNAN BERSEJARAH DI KOTA METRO SEBAGAI SUMBER BELAJAR SEJARAH LOKAL KELAS X SMA NEGERI 2 METRO - Tri Hidayanti; Bobi Hidayat (Swarnadwipa, 2020)
This study aims to produce learning resources that take advantage of technological advances in the form of a digital encyclopedia of historical buildings in Metro City. The development model used in this research is a development adapted from Sugiyono level 1 research, consisting of 5 stages, namely (1) analysis of potentials and problems, (2) data collection, (3) product design, (4) design and material validation, (5) ) design and material improvements. The digital encyclopedia of historical buildings produced has gone through two stages of validation and revision. The first material expert validation got an average score of 81.87% while the design expert was 92%. Even though these results are already very good, there are some expert suggestions to get even better products, so that the second stage of revision and validation is carried out which gets a score of 92.5% for material experts and 94% for design experts. After the revision, the product got a score increase of 10.63% in material validation and 2% in design validation. The resulting product is very good so that a small group trial can be carried out on 10 class X students of SMAN 2 Metro and get a result of 87.5%. The results of product trials show that the product is suitable for use in the learning process and can be a learning resource for teachers and students to use this digital encyclopedia.